2007
DOI: 10.1110/ps.062664107
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor–ligand complexes measured by chip‐based nanoelectrospray mass spectrometry: An approach for the screening of endocrine disruptors

Abstract: In the present report, a method based on chip-based nanoelectrospray mass spectrometry (nanoESI-MS) is described to detect noncovalent ligand binding to the human estrogen receptor a ligand-binding domain (hERa LBD). This system represents an important environmental interest, because a wide variety of molecules, known as endocrine disruptors, can bind to the estrogen receptor (ER) and induce adverse health effects in wildlife and humans. Using proper experimental conditions, the nanoESI-MS approach allowed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 62 publications
4
46
1
Order By: Relevance
“…However, when the interaction in solution is determined by the entropy-driven hydrophobic effect, nanoESI-MS fails to give accurate results representative of the solution equilibria. Similar findings have been reported by other groups [16], including the study of hydrophobic ligands binding to protein targets [13][14][15]. If mixed polar/hydrophobic interactions are present (GST), the majority of the complex survives the transfer from solution into gas phase, most likely due to the polar fraction [16].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, when the interaction in solution is determined by the entropy-driven hydrophobic effect, nanoESI-MS fails to give accurate results representative of the solution equilibria. Similar findings have been reported by other groups [16], including the study of hydrophobic ligands binding to protein targets [13][14][15]. If mixed polar/hydrophobic interactions are present (GST), the majority of the complex survives the transfer from solution into gas phase, most likely due to the polar fraction [16].…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, there is some evidence that hydrophobic contributions do affect the gas-phase stability of complexes, although this is observed only in combination with electrostatic interactions [12]. Complexes that exist in solution mainly due to hydrophobic effects are likely to dissociate in the gas phase [11,[13][14][15][16]. When studying noncovalent complexes by ESI-MS, it is known that by increasing the ionic strength or adding organic solvents to the aqueous buffer will affect the hydrophobic effect in solution [17].…”
mentioning
confidence: 99%
“…Advantages of nanoESI include improved desolvation, greater salt tolerance, and higher ion yield [32,41,42]. However, nanoESI tends to be less robust in terms of signal stability and reproducibility than regular ESI [43,44]. It is often implied that nanoESI is better suited for preserving proteinligand interactions [32,45], although experimental evidence suggests that this is not necessarily the case [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Several reports have shown that MS can be used to characterize the binding of drugs to target enzymes in terms of stoichiometry, specificity, and stability. 29,30) This method is advantageous because it requires small sample amounts. Because of its rapidity, sensitivity, and ability to directly determine binding stoichiometry, MS is potentially applicable as a superior high-throughput screening method for developing anti-HIV drugs.…”
mentioning
confidence: 99%